Loss of COMT activity reduces lateral root formation and alters the response to water limitation in sorghum brown midrib (bmr) 12 mutant. Issue 5 (4th December 2020) - Saluja, Manny; Zhu, Feiyu; Yu, Hongfeng; Walia, Harkamal; Sattler, Scott E.
Summary: Lignin is a key target for modifying lignocellulosic biomass for efficient biofuel production. Brown midrib 12 ( bmr12 ) encodes the sorghum caffeic acid O‐methyltransferase (COMT) and is one of the key enzymes in monolignol biosynthesis. Loss of function mutations in COMT reduces syringyl (S) lignin subunits and improves biofuel conversion rate. Although lignin plays an important role in maintaining cell wall integrity of xylem vessels, physiological and molecular consequences due to loss of COMT on root growth and adaptation to water deficit remain unexplored. We addressed this gap by evaluating the root morphology, anatomy and transcriptome of bmr12 mutant. The mutant had reduced lateral root density (LRD) and altered root anatomy and response to water limitation. The wild‐type exhibits similar phenotypes under water stress, suggesting that bmr12 may be in a water deficit responsive state even in well‐watered conditions. bmr12 had increased transcript abundance of genes involved in (a)biotic stress response, gibberellic acid (GA) biosynthesis and signaling. We show that bmr12 is more sensitive to exogenous GA application and present evidence for the role of GA in regulating reduced LRD in bmr12 . These findings elucidate the phenotypic and molecular consequences of COMT deficiency under optimal and water stress environments in grasses.